The optimal PEEP after alveolar recruitment maneuver assessed by electrical impedance tomography in healthy horses - Andrade, Felipe Silveira Rego Monteiro; Ambrósio, Aline Magalhães; Rodrigues, Renata Ramos; Faccó, Lara Lopes; Gonçalves, Lucas Alaião; Garcia Filho, Sérgio Grandisoli; dos Santos, Rosana Thurler; Rossetto, Thais Colombo; Pereira, Marco Aurélio Amador; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2022)
Electrical impedance tomography has been an important tool for assessing pulmonary ventilation in several situations, such as the alveolar recruitment maneuver in PEEP titration to maintain the lungs open after atelectasis reversion. In the same way as in humans and dogs, in horses, this tool has been widely used to assess pulmonary aeration undergoing anesthesia, mechanical ventilation, recruitment maneuver, standing horses, or specific procedures. The present study aimed to evaluate the distribution of regional ventilation during ARM based on lung monitoring assessment by EIT, focusing on better recruitment associated with less or no overdistention. Fourteen horses of 306  21kg undergoing isoflurane anesthesia in dorsal recumbency were used. The animals were mechanically ventilated with a tidal volume of 14 mL/kg and respiratory rate of 7-9. An alveolar recruitment maneuver was instituted, increasing the PEEP by five cmH2O every 5 minutes until 32 cmH2O and decreasing it by 5 cmH2O every 5 minutes to 7 cmH2O. Arterial blood samples were collected for blood gas analysis, EIT images, hemodynamic, and respiratory mechanics at each step of PEEP. Associated with the CoV-DV increase, there was a significant decrease in the DSS during the ARM compared to baseline, and there was a significant increase in the NSS when PEEP was applied above 12 cmH2O. The ComplROI showed a significant increase in the dependent area and a significant decrease in the non-dependent area during ARM. The Drive Pressure decreased significantly during the ARM, and Cst, PaO2, and PaO2/FiO2 ratio increased significantly. The VD/VT decreased significantly at DEPEEP17 and DEPEEP12. There was HR increase at INPEEP27, INPEEP 32, and DEPEEP17 (p < 0.0001; p < 0.0001; e p < 0.05, respectively), those values being above the normal for the species. The MAP had a significant decrease in INPEEP32, which was also observed in relation to CO (p < 0.01). The ARM by PEEP titration applied in the present study showed better ventilation distribution associated with aeration migration to dependent lung areas, with minimal overdistention of the previously aerated alveolus between PEEP 17 and 12 cmH2O decreasing step.